Causes of microcephaly in human—theoretical considerations - Heide, Michael; Huttner, Wieland B. (Frontiers in Neuroscience, 2023)
As is evident from the theme of the Research Topic "Small Size, Big Problem: Understanding the Molecular Orchestra of Brain Development from Microcephaly", the pathomechanisms leading to mirocephaly in human are at best partially understood. As molecular cell biologists and developmental neurobiologists, we present here a treatise with theoretical considerations that systematically dissect possible causes of microcephaly, which we believe is timely. Our considerations address the cell types affected in microcephaly, that is, the cortical stem and progenitor cells as well as the neurons and macroglial cell generated therefrom. We discuss issues such as progenitor cell types, cell lineages, modes of cell division, cell proliferation and cell survival. We support our theoretical considerations by discussing selected examples of factual cases of microcephaly, in order to point out that there is a much larger range of possible pathomechanisms leading to microcephaly in human than currently known.